PROBLEM METODOLOGIS PEMBENTUKAN KARAKTER SISWA DI MADRASAH - Meli Nazila; Kharisma Putri Anggraini; M. Hafidz Abinaya; M. Husin Baihaqi; Abudurrahmansyah Abudurrahmansyah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Education plays a crucial role in shaping knowledgeable and morally upright individuals, with madrasahs as strategic institutions that instill Islamic values. However, the process of character formation in madrasahs still faces methodological challenges, particularly in the alignment of learning methods with students' needs in the modern era. A literature review using a descriptive qualitative approach found that teachers often lack innovation in selecting effective strategies, resulting in inadequate internalization of character values. Other challenges, such as media influence, promiscuity, and misuse of technology, exacerbate this situation. Therefore, a more adaptive and contextual approach is needed through teacher role models, positive habits, and the integration of moral values ??into all madrasah activities to achieve effective and sustainable character education.